Valoración económica del secuestro de CO2 en un bosque de colina baja de la concesión forestal 16-IQU/C-J-224-04, distrito de Pebas, Loreto. 2021 - Talexio Lopez, Franck David (2021)
The economic value of the CO2 sequestration provided by the tree species of the low-hill forest of the Pebas district, Loreto, was quantified in this study. The database of the forest census of commercial forest species from forest concession 16-IQU/C-J-224-04 was used. The results show that the economic value of CO2 sequestration in the commercial forest species of the evaluated forest is USD 3757,16/ha. V. vismiifolia with USD 536,40/ha and B. excelsa with USD 337,22/ha are the species with the highest contribution, while C. chrysocalyx with USD 21,20/ha and C. racemosa with USD 19,76/ha shows the lowest contributions. Statistically, a significant difference (?= 0,05) there exist in the economic value of CO2 sequestration among commercial species.